Table of Content - - (Journal of engineering sciences and information technology, 2025)
:Table of Content• The impact of the Vision 2030 projects on contemporary architecture: Analytical study of Saudi architecture mapEng. Nazar Mohamed Elkheir Mohamed Osman• Surface Analysis Using Cloud Computing: An Applied Study on the Google Earth Engine PlatformDr. Nadiah Awad Al-Safri• Smart Tourism and Environmental Sustainability: A Descriptive and Analytical Case Study of Saudi ArabiaEng. Ashraf Fawzy Hassan• Integration of Industrial and Surgical Robotic Systems: A Case Study of Combining the SCARA Robot with the Da Vinci RobotAsst-Prof. Lara Fathi Kadid, Lecturer. Hasan Khaled Kazzaz, Eng. Mohamad Adib Mohamad Taki Eddin Issa• Smart Recommendation System for TouristsNour Abd Alhameed Khallof, Dr. Majida Albakoor
Keywords: Journal of Engineering Sciences and Information Technology